PENGARUH KEPUASAN KONSUMEN TERHADAP LOYALITAS BERBELANJA PADA HERMES PALACE MALL BANDA ACEH - Yusra Yusra (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2015)
The objective of this research is to know the influence of customer satisfaction and its factors that influence customer loyalty in Hermes Palace Mall Banda Aceh. The samples in this research are all the customer of Hermes Palace Mall Banda Aceh, which is 100 of the customers, are the respondent. The respondents were taken by incidentally sampling technique. To know the influences of independent variable to dependent variable, the collected data were analyzed by using simple linear regression method with SPSS version 15.0. The data analysis shows the customer satisfaction in shopping is significantly influenced the loyalty of the customer. The “t” value is 2,626 with the significance level at 0,013. It also shows the relationship between the customer satisfactions and the increased in sales in Hermes Palace Mall Banda Aceh is relatively low So, to enhance the customer loyalty, the company manager should increase the service quality. Because that is the important factor which will determine the customer satisfaction in shopping, besides other factor such as prizing, product quality and social factor.